PROBLEMATIKA IMPLEMENTASI KURIKULUM PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Ramadhan, Harimas; Deriwanto, Deriwanto; Harmi, Hendra (STAI Ma'had Aly Al-Hikam Malang, 2023)
This research discusses the implementation of the 2013 curriculum in Islamic Religious Education (PAI) teaching. The implementation of the 2013 curriculum requires optimal cooperation among teachers, involving teamwork and compact collaboration. In this study, the author explains the concept of curriculum implementation, the requirements of teachers in Islam, the duties and roles of PAI teachers, and the teachers' abilities in implementing the 2013 curriculum. This research also discusses the stages of planning and implementation of teaching in the 2013 curriculum, including introductory activities, core activities, and closing activities. This study is a descriptive research that aims to provide descriptions of situations or events. The author uses a qualitative descriptive approach in this research. The results of this study indicate that the implementation of the 2013 curriculum in PAI teaching requires collaboration among all stakeholders, including teachers, schools/madrasas, and the educational environment. Furthermore, this research emphasizes the importance of the teacher's role in shaping the character and competence of students while considering the diversity of individuals in learning.